Acne Vulgaris between Der. Pts in Palestine 2000-2009 - Dr. Hisham Arda (My University, 2010)
Acne Vulgaris is primarily a chronic inflammatory process of the pilosebaceous unit, clinical presentation as comedones (open=blackheads, closed=white heads), papules, pustules or even cystic lesions in the face, chest, shoulders and upper back.
Acne is the commonest skin compliant as it affects up to 70-85% of adolescents, only 10-20% of them request medical advice. Symptoms of acne may begin at the age of 8-12 years but usually at 15-18ys and began to involute by the age of 25, but 10-12% of females and 3% of males continue to have clinical acne until 45 years of age [1,5].
The aim of this retrospective study was to evaluate the incidence of acne between dermatology patients in Palestine.
Materials & Methods : we looked through our records during 2000-2009 and collected data of acne patients seen during this period.
Results : During this period we had treated 5528 persons complaining of acne (1674 males and 3854 females). Table 1 shows the year distribution of acne patients and they constituted 9-12% of our Dermatology patients.
Table 2 shows the age distribution of 727 acne pts (215 males & 512 females) seen during 2009. Acne presents in some of our patients by the age of 10ys but most of them were between the age of 16-25ys (531 /727) and 39 females had acne lesions between 31-50ys as pustules mainly in the chin but just few males had acne lesions above 30ys of age in the shoulders and back.
Table 3 shows the month distribution of acne patients during 2009 and revealed that acne pts report all the year and most of them report more regularly than other Der. pts. for periods more than 1 year.
Discussion :
Acne is a common complaint between Der. pts. in Palestine (9-12%). Females report more frequently than males 5:2, most of the patients presented by the age of (16-25ys) with mild to moderate degree of acne. Many of the female patients are psychologically disturbed and need special attention and enough time to explain that acne will involute by time and it is very important to avoid squeezing of lesions which may lead to permanent scaring.
In the management of acne we depend on using systemic antibiotics as Tetracycline 500ml/d, Doxycycline, Azithromycine or Erythromycin. Local treatment in the form of Benzoil peroxide 5-10%, Clindamycin, Erythromycin or Azaleic acid [1,3,4]. Tritinoids locally are helpful in dealing with comedones. Systemic Isotritinoid is used only in severe cases of pustules or nodulocystic Acne.
Summary :
5528 (1674 males & 3854 females) acne patients were seen by us in Palestine during the period 2000-2009 which forms 9-12% of our dermatology patients. Acne was one of the most common skin diseases in Palestine [2]. Male to female ratio between our patients was 2:5. Most of our patients were between the age of 16-25ys (531/727) during 2009. Traditional methods of treatment were enough for management of most of the patients. Systemic Isotritinoin was only used in severe cystic and nodulocystic acne. Further studies are needed to evaluate the incidence of acne in the Palestinian community.

Acne Vulgaris is primarily a chronic inflammatory process of the pilosebaceous unit, clinical presentation as comedones (open=blackheads, closed=white heads), papules, pustules or even cystic lesions in the face, chest, shoulders and upper back.
Acne is the commonest skin compliant as it affects up to 70-85% of adolescents, only 10-20% of them request medical advice. Symptoms of acne may begin at the age of 8-12 years but usually at 15-18ys and began to involute by the age of 25, but 10-12% of females and 3% of males continue to have clinical acne until 45 years of age [1,5].
The aim of this retrospective study was to evaluate the incidence of acne between dermatology patients in Palestine.
Materials & Methods : we looked through our records during 2000-2009 and collected data of acne patients seen during this period.
Results : During this period we had treated 5528 persons complaining of acne (1674 males and 3854 females). Table 1 shows the year distribution of acne patients and they constituted 9-12% of our Dermatology patients.
Table 2 shows the age distribution of 727 acne pts (215 males & 512 females) seen during 2009. Acne presents in some of our patients by the age of 10ys but most of them were between the age of 16-25ys (531 /727) and 39 females had acne lesions between 31-50ys as pustules mainly in the chin but just few males had acne lesions above 30ys of age in the shoulders and back.
Table 3 shows the month distribution of acne patients during 2009 and revealed that acne pts report all the year and most of them report more regularly than other Der. pts. for periods more than 1 year.
Discussion :
Acne is a common complaint between Der. pts. in Palestine (9-12%). Females report more frequently than males 5:2, most of the patients presented by the age of (16-25ys) with mild to moderate degree of acne. Many of the female patients are psychologically disturbed and need special attention and enough time to explain that acne will involute by time and it is very important to avoid squeezing of lesions which may lead to permanent scaring.
In the management of acne we depend on using systemic antibiotics as Tetracycline 500ml/d, Doxycycline, Azithromycine or Erythromycin. Local treatment in the form of Benzoil peroxide 5-10%, Clindamycin, Erythromycin or Azaleic acid [1,3,4]. Tritinoids locally are helpful in dealing with comedones. Systemic Isotritinoid is used only in severe cases of pustules or nodulocystic Acne.
Summary :
5528 (1674 males & 3854 females) acne patients were seen by us in Palestine during the period 2000-2009 which forms 9-12% of our dermatology patients. Acne was one of the most common skin diseases in Palestine [2]. Male to female ratio between our patients was 2:5. Most of our patients were between the age of 16-25ys (531/727) during 2009. Traditional methods of treatment were enough for management of most of the patients. Systemic Isotritinoin was only used in severe cystic and nodulocystic acne. Further studies are needed to evaluate the incidence of acne in the Palestinian community.
Acne Vulgaris between Der. Pts in Palestine 2000-2009